Lepidium meyenii (maca) and soy isoflavones reduce cardiac stunning of ischemia-reperfusion in rats by mitochondrial mechanisms - Colareda, German Andres (2021)
Background and aim: Phytoestrogens are traditionally used for cardiovascular risks but direct effects on the ischemic heart remain unclear. Plants with phytoestrogens are used for reducing menopausic symptoms and they could also be cardioprotectives. Here we investigated whether maca (Lepidium meyenii) contains isoflavones and prevents cardiac stunning, in comparison to soy isoflavones. Experimental procedure: Both products were orally and daily administered to rats during 1 week before exposing isolated hearts to ischemia/reperfusion (I/R). Young male (YM), female (YF) and aged female (AgF) rats treated with maca (MACA, 1 g/kg/day) or soy isoflavones (ISOF, 100 mg/kg/day) were compared to acute daidzein (DAZ, 5 mg/kg i.p.) and non-treated rat groups. Isolated ventricles were perfused inside a calorimeter to simultaneously measure contractile and calorimetrical signals before and during I/R. Results and conclusions: Maca has genistein and daidzein. MACA and ISOF improved the post-ischemic contractile recovery (PICR) and muscle economy (P/Ht) in YM and YF hearts, but not in AgF hearts. DAZ improved PICR and P/Ht more in YM than in YF. The mKATP channels blockade reduced both PICR and P/Ht in DAZ-treated YM hearts, without affecting them in ISOF or MACA-treated YM hearts. In MACA treated YF hearts, the simultaneous blockade of NOS and mKATP channels, or the mNCX blockade reduced cardioprotection. Results show that subacute oral treatment with maca or with soy isoflavones was strongly preventive of cardiac ischemic dysfunction, more than the acute administration of a pure isoflavone (daidzein, genistein). Maca induced synergistic and complex mechanisms which prevented mitochondrial calcium overload.